Influence on turnover in the housekeeping department: a case of some selected hotels in Bolgatanga Municipality - Catherine Fuseini; Ellen Olu Fagbemi; Joshua Awuni (Cactus, 2024)
In the competitive business world, employee turnover has been a pressing issue facing organisations around the world. The study sought to investigate the influence on turnover in the housekeeping department of some selected hotels in Bolgatanga municipality. A descriptive survey design was used. The population of the study comprised 200 employees from the housekeeping department of five hotels in Bolgatanga Municipality. The study used purposive and simple random sampling to select 100 housekeeping employees and 40 hotel management employees. The main instrument used in this study was the questionnaire. Descriptive statistics such as mean and standard deviation were used to summarise the data. The study revealed high employee turnover in the housekeeping department of hotels in Bolgatanga municipality. It was revealed that 3-4 employees leave the housekeeping department of the sampled hotels in Bolgatanga Municipality every year. The results show that employees' expectations are a major determinant of turnover in the housekeeping department of hotels in Bolgatanga municipality. The study revealed that employee expectations have a significant influence on employee turnover in the housekeeping department (p<0.01). It was concluded that improving the employee benefit package, paying employees more and providing more flexible working hours would solve the problem of employee turnover in the housekeeping department of the hotels. It was recommended that hotel industry management should endeavour to use the interview as a tool during the hiring process to understand the job expectations of employees and that the qualified candidates whose job expectations can be met by the hotel should be hired.